Modelling Of The Friction Welding Process Between Mild Steel And Alumina - Seli, Hazman (2011)

(untitled)
The heat transfer, mass diffusion and thermo-mechanical mechanisms in friction welding (FW) are not fully understood. In friction welding of two dissimilar materials, two rods are welded together by holding one of them still rotated while the other under the influence of an axial load which creates frictional heat in the interface. This thesis reports a study of the thermal, thermo-mechanical and mass diffusive behaviors of friction welded alumina–mild steel rods with the use of aluminum alloy sheet as interlayer.